Պատմության և հասարակության ուսումնասիրության մեթոդները - Գ. Ռ. Ամիրյան (ՀՀ ԳԱԱ հրատ.)
Анализ исторической теории, общественных, исторических явлений и событий, а также изучение человеческого поведения и деятельности предполагаетприменениесоответствующего методологического подхода и определенных методов: комплексного, познавательного,аналитического, исторического, логического, обобщающего, индивидуального и метода изучения общества.The theoretical analysis of history, the research of social phenomena, events and facts, human activities and behaviour assume corresponding methodical approach, certain use of methods. Some of these methods are: the research structural method of society, cognitive method, analytical method, historical method, logical method, generalizing method and individual method.
Keywords: History; B Philosophy; Psychology; Religion; B Philosophy; D History; H Social Sciences